Penerapan Rice Transplanter Semi Otomatis untuk Meningkatkan Efisiensi dan Produktivitas Pertanian dalam Mendukung Keberlanjutan Ketahanan Pangan - Luthfi; Marlina, Lilis; Erliana, Hilma; Wulan Sari, Intan; Hasan, Riza; Akhyat, Fathur (PELITA NUSA TENGGARA, 2025)
This Community Service Program (PKM) is motivated by the problems of low productivity and inefficiency of rice farming in Woyla Barat District due to reliance on manual planting methods, high labor costs, and minimal technology adoption. The program aims to enhance production efficiency through the implementation of semi-automatic rice transplanters, reduce production costs, and strengthen farmers' capacity based on Islamic economic principles. The implementation method consists of five stages: socialization, technical training, technology application, mentoring, and sustainability evaluation, using a participatory approach involving 10 farmers from the Berkah Bersama Farmers Group. The results demonstrate significant efficiency improvements: cost savings of up to 77%, reduction in planting time from 6 days to 1 day per hectare, decrease in labor requirements by up to 83%, and increased crop productivity by 15–25%. The program also strengthened the farmers' group institution through a sharia-based cooperative model and the internalization of values such as justice, efficiency, and gratitude. The implication is the creation of a sustainable agricultural system that integrates modern technology with Islamic values, supporting local food security. The program concludes that the integration of technology and a sharia-based approach can economically and socially empower farmers, with potential for replication in other regions.